Extended molecular dynamics of a c-kit promoter quadruplex - Islam, Barira; Stadlbauer, Petr; Krepl, Miroslav; Koca, Jaroslav; Neidle, Stephen; Haider, Shozeb; Sponer, Jiri (Nucleic acids research, 2015)
The 22-mer c-kit promoter sequence folds into a parallel-stranded quadruplex with a unique structure, which has been elucidated by crystallographic and NMR methods and shows a high degree of structural conservation. We have carried out a series of extended (up to 10 μs long, ∼50 μs in total) molecular dynamics simulations to explore conformational stability and loop dynamics of this quadruplex. Unfolding no-salt simulations are consistent with a multi-pathway model of quadruplex folding and identify the single-nucleotide propeller loops as the most fragile part of the quadruplex. Thus, formation of propeller loops represents a peculiar atomistic aspect of quadruplex folding. Unbiased simulations reveal μs-scale transitions in the loops, which emphasizes the need for extended simulations in studies of quadruplex loops. We identify ion binding in the loops which may contribute to quadruplex stability. The long lateral-propeller loop is internally very stable but extensively fluctuates as a rigid entity. It creates a size-adaptable cleft between the loop and the stem, which can facilitate ligand binding. The stability gain by forming the internal network of GA base pairs and stacks of this loop may be dictating which of the many possible quadruplex topologies is observed in the ground state by this promoter quadruplex.
Keywords: Cations; Molecular Dynamics Simulation; Sodium; draslík; G-kvadruplexy; párování bází; Base Pairing; protoonkogenní proteiny c-kit; denaturace nukleových kyselin; promotorové oblasti (genetika); simulace molekulární dynamiky; kationty; G-Quadruplexes; Nucleic Acid Denaturation; sodík; Promoter Regions, Genetic; Potassium; Proto-Oncogene Proteins c-kit